Applying the Principles of Restraint of the Senses with Living with the Lifestyle - (Donkamonkan), Phramaha Tanakorn Katapouyo; Thitapañño, Phramaha Mit; Krairach, Thaksina (Dhammathas Academic Journal, 2019)
Sense-control, it is a practice to be conscious. Emotional Intelligence To not be harmed. Amuse and dislike and can cut that makes the pleasing. And the displeasure to go out quickly. This is a protection from the beginning to the end does not cause sin no harm. And do not come up with suffering and follow the application of sense-control and Lifestyle. From the ear, nose, tongue, tongue, body because of sense cause of passion. The sense-control is a good concentration. Will do any business. Does it for a reason? The successor goodwill determines what the truth is clear. The world and the right way to have sense-control, it must be conscious. Be prepared always, it must be trained by training to have consciousness is a basic knowledge and practice is always. When emotions effect on the 6 sense-door, 6 sense development, the quality is used to bring peace to the called a sense development, people who practice well. It is safe from sin and from the suffering that is born of passion.